2022
DOI: 10.3389/fchem.2022.988459
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory activity of constituents isolated from Dendrobium nobile (Lindl.)

Abstract: Dendrobium nobile (Lindl.) have long been used as herbal tea and a traditional herbal medicine to treat Alzheimer’s disease (AD). In the current study, nineteen compounds (1–19), including two new vitamin E homologues (1–2), one new sesquiterpene (6), and two new dendrobines (7, 8), were isolated and identified from stems of Dendrobium nobile. Their structures were elucidated on the basis of NMR, 13C NMR calculation, and DP4+ probability analyses. The absolute configurations of new compounds were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Dendrobium nobile Lindl. is a herb that is grown in Southwest China, such as Guizhou, Sichuan, and Guangxi Provinces ( Adhikari et al., 2020 ), and plays a vital role in enhancing health with properties such as neuroprotection ( Li et al., 2022a ; Li et al., 2022b ), anti-inflammation ( Lei et al., 2022 ), antioxidation ( Long et al., 2023 ), and immune modulation ( Fan et al., 2020 ; Long et al., 2023 ). Studies have shown that D. nobile is rich in chemical components such as alkaloids, polysaccharides, phenolic acids, and flavonoids ( Ling et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dendrobium nobile Lindl. is a herb that is grown in Southwest China, such as Guizhou, Sichuan, and Guangxi Provinces ( Adhikari et al., 2020 ), and plays a vital role in enhancing health with properties such as neuroprotection ( Li et al., 2022a ; Li et al., 2022b ), anti-inflammation ( Lei et al., 2022 ), antioxidation ( Long et al., 2023 ), and immune modulation ( Fan et al., 2020 ; Long et al., 2023 ). Studies have shown that D. nobile is rich in chemical components such as alkaloids, polysaccharides, phenolic acids, and flavonoids ( Ling et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is classified as a superior product in “Shen Nong’s Herbal Classic” because of its excellent tonic properties in alleviating paralysis, lowering Qi, and tonifying the weakness of the internal organs. Previous studies on DNL have mainly focused on its small molecule components, such as phenols, alkaloids, and sesquiterpenes [ 15 , 16 , 17 , 18 ], while only a few studies have investigated its bioactive macromolecules. DNL polysaccharides (DNPs) are among the main active components of DNL, exerting antioxidant [ 19 ], anti-inflammatory [ 17 ], and anti-apoptotic effects [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dendrobium contains several bioactive metabolites including: polysaccharides, alkaloids, flavonoids, amongst others ( He et al., 2020 ; Lu et al., 2022 ). These components offer various health benefits, such as antioxidation, anti-inflammation, and antitumor effects ( Lei et al., 2022 ), improvement of liver damage, and nerve protection ( Li D. et al., 2022 ). Our research group discovered variant strains of D. nobile L. that bloom pure white flowers under the same ecological conditions in which the flowers are typically purple and white.…”
Section: Introductionmentioning
confidence: 99%